Caracterização dos ciclos de negócios nos setores produtivos da indústria brasileira - Gadelha, João Lima da Costa (2017)
This paper examines the business cycle characteristics of Brazil's industrial sector from 1995 to 2016. From the Burns and Mitchell specification the empirical analysis adopted the Baxter-King filter to decompose the industrial sub-sectors in trend and cycle. The decomposition carried out confirmed the hypothesis that the cycle of the Mineral Extractive Sector was the most volatile of the analyzed ones, also presenting a transient behavior independent of the others. The results in the time domain point out that the short-term fluctuations of the Electricity, Gas, Water, Sewage and Urban Cleaning series have predictive capacity over the cycle of the Civil Construction sector. On the other hand, the Manufacturing Industry and Total Industry series have a pro-cyclical behavior against transient shocks, being strongly synchronized.